Cognitive Development of Mathematics Education Students based on Piaget's Theory in terms of Gender Differences - Laja, Yosepha Patricia Wua; Hijriani, Lailin (Kreano, Jurnal Matematika Kreatif-Inovatif, 2022)
This study aims to understand the cognitive development of mathematics education students based on Piaget's theory in terms of gender differences. This research method is descriptive quantitative research with the research subjects being students of mathematics education at Timor Universities. Students' cognitive development was measured using the Logical Operations Test (LOT), which consisted of 14 numbers. LOT questions are given to students, the results are analyzed and described. The results showed that the cognitive development stage for females was 19.18% in the initial concrete stage, 36.99% in the final concrete stage, 13.70% in the initial formal stage and 1.37% in the final formal stage. Male at 9.59% in the initial concrete stage, 6.85% in the final concrete stage, 9.59% in the initial formal stage and 2.74% in the final formal stage. Meanwhile, students' understanding based on seven logical operations is in low understanding for each type.Penelitian ini bertujuan untuk  mengetahui perkembangan kognitif mahasiswa pendidikan matematika berdasarkan teori Piaget ditinjau dari perbedaan jenis kelamin. Metode penelitian ini adalah penelitian deskriptif kuantitatif dengan subjek penelitian adalah mahasiswa pendidikan matematika Universitas Timor. Perkembangan kognitif mahasiswa diukur dengan menggunakan Tes Operasi Logis (TOL) yang berjumlah 14 nomor. Soal TOL diberikan kepada mahasiswa, hasilnya dianalisis dan dideskripsikan. Hasil penelitian menunjukkan bahwa tahap perkembangan kognitif sebesar 19,18% tahap konkret awal, 36,99 % tahap konkret akhir, 13,70% tahap formal awal dan 1,37% tahap formal akhir bagi mahasiswa perempuan. Sementara hasil pemetaan tahap perkembangan kognitif sebesar 9,59% tahap konkret awal, 6,85 % tahap konkret akhir, 9,59% tahap formal awal dan 2,74% tahap formal akhir bagi mahasiswa laki-laki. Sementara itu pemahaman mahasiswa berdasarkan 7 operasi logis berada dalam pemahaman rendah untuk masing-masing tipe.